Faktor-Faktor yang Mempengaruhi Pendapatan Nelayan Tangkap di Desa Tabanio Kecamatan Takisung Kabupaten Tanah Laut - Sailluddin, Muhammad (PPJP ULM, 2018)
This research was conducted to know: the cost factor of care, operationalcost, depreciation cost, and the means of catching together to income and learn themost dominant factor influence the catching fisherman income in Tabanio Village,Takisung Sub-District, Tanah Laut Regency.This thesis research uses a quantitative method with numbers such asmaintenance cost, operational cost, fishing gear, and depreciation cost. Meanwhile, thedata used to analyze the thesis is using cross-section data. With primary material thatis taken a direct data from the source, that is obtained from candid interviews from afishing boat owner in Tabanio Village, Takisung District, Tanah Laut Regency.After doing research, it is known that simultaneously the cost factor of care,operational cost, depreciation cost, and fishing gear effect on to catch fishermanincome and appliance catch variable (X3) is the factor which has the most dominantinfluence to acquire fisherman's income in Tabanio Village, Takisung District TanahLaut District.